2004
DOI: 10.1074/jbc.m313764200
|View full text |Cite
|
Sign up to set email alerts
|

Development of Protein-based Inhibitors of the Proprotein of Convertase SKI-1/S1P

Abstract: Processing of membrane-bound transcription factors such as sterol regulatory element-binding proteins (SREBPs) and the ER-stress response factor ATF6, and glycoproteins of some hemorrhagic fever viruses are initiated by the proprotein convertase SKI-1/S1P. So far, no cellular protein-based inhibitor of the hydrophobicamino acid specific SKI-1 is known. The prosegment of the basic-amino acid specific convertases (e.g. furin and PC5) or ␣ 1 -PDX, a variant of ␣ 1 -antitrypsin (␣ 1 -AT) exhibiting an RIPR 358 seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 64 publications
(92 reference statements)
2
60
0
Order By: Relevance
“…Cell lysates were incubated (24 h, 37°C, pH 5.8) with 35 Slabeled ECM. The medium was centrifuged, and the supernatant containing the sulfate-labeled degradation fragments was analyzed by gel filtration on a Sepharose CL-6B column (0.9 ϫ 30 cm).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell lysates were incubated (24 h, 37°C, pH 5.8) with 35 Slabeled ECM. The medium was centrifuged, and the supernatant containing the sulfate-labeled degradation fragments was analyzed by gel filtration on a Sepharose CL-6B column (0.9 ϫ 30 cm).…”
Section: Methodsmentioning
confidence: 99%
“…We have also substituted the conserved Arg 153 with glutamine, assuming that it may constitute a potential RXXX2 recognition motif for a subtilisin/kexin isozyme-1 convertase (33)(34)(35). Again, the R153A mutant (mutation #10) was found to be normally processed and enzymatically active (Fig.…”
Section: Processing Of Human Heparanase At Site 1-mentioning
confidence: 99%
See 1 more Smart Citation
“…The data demonstrated that PCs only process proPDGF-B at the RGRR 81 k site in HK293 cells (Figure 2). Furthermore, the expression of SKI-1 in LoVo-C5 cells did not enhance processing (Figure 2), nor was the C-terminal processing PDGF-B abrogated in SKI-1-deficient CHO cells (Pullikotil et al, 2004) (not shown). Since NARC-1/PCSK9 is not expressed in HK293 cells , the above results rule out the implication of any member of the PC-family in this C-terminal processing event.…”
Section: Discussionmentioning
confidence: 99%
“…The culture media contained 145-kDa SKI-1 precursor and a 50-kDa fragment band. Due to the specificity of the antibody and the structure of SKI-1 (31,32,38,39), we assume that all forms detected (145, 105, 70, and 50 kDa) contain the transmembrane sequence and are associated with membranes or vesicles released from cells. Interestingly, the amount of 50-kDa band in the media was found to be lower in mineralized cultures, indicating that breakdown of SKI-1 may be increased under non-mineralizing conditions (Fig.…”
Section: Activated 105-kda Form Of Ski-1 Is Present In Biomineral-mentioning
confidence: 99%